Explorations of the Syntax-Semantics Interface - Bohnemeyer, Jürgen; Butler, Lindsay K.; Everett, Caleb; Fleischhauer, Jens; Fleischhauer, Jens; Foley, William A.; Hammond, Jeremy; Himmelmann, Nikolaus P.; Jaeger, T. Florian; Koenig, Jean-Pierre; Latrouite, Anja; Latrouite, Anja; et al. (düsseldorf university press, 2016)
The articles in this volume present original research on the encoding of meaning in a variety of constructions and languages. Many of the contributions take the framework of Role and Reference Grammar as a point of reference, either by applying it to the analysis of linguistic data or by discussing, extending, and challenging some of its assumptions. The topics of the articles range from general questions concerning the relation of meaning and its syntactic realization to the study of specific grammatical phenomena in a number of typologically diverse languages, including Yucatec Maya, Kabardian, Tagalog, Murik-Kopar, Avatime, Whitesands, Tundra Yukaghir, and various Indo-European languages. The articles will be of interest to researchers and advanced students working on the interface between syntax, semantics and pragmatics. This series 'Studies in Language and Cognition' explores issues of mental representation, linguistic structure and representation, and their interplay. The research presented in this series is grounded in the idea explored in the Collaborative Research Center 'The structure of representations in language, cognition and science' (SFB 991) that there is a universal format for the representation of linguistic and cognitive concepts
Keywords: Semantics; Constructional Schemata; Linguistic Categories; linguistic theory; syntax-semantics interface; Sémantique; Syntaxe; Grammar, Comparative and general; LANGUAGE ARTS & DISCIPLINES / General; semantics; Grammar, Comparative and general -- Syntax; Semantik; Syntax; Role and Reference Grammar; Avatime; Caleb Everett; Carlos Periñán-Pascual; constructional schemata; degree expressions; Dejan Matic; Deutsche Forschungsgemeinschaft; DFG.; diasystematic approach; Eunkyung Yi; FunGramKB Grammaticon; Gerhard Schurz; Gisa Rauh; Hana Filip; Heinrich-Heine-Universität Düsseldorf; integrated dislocation; Jean-Pierre König; Jeremy Hammond; John Peterson; Jürgen Bohnemeyer; Kabardian Involuntative; Laura Kallmeyer; LD.; left Dislocation; lexical representation of verbs; Lindsay K. Butler; linguistic categories; lingustic theory; multilectalism; multilingualism; Murik-Kopar; Nikolaus P. Himmelmann; non-integrated dislocation; Noun Phrase Structure; Peter Indefrey; Ranko Matasovic; register variation; Ricardo Mairal; Robert D. Van Valin, Jr; RRG.; Saskia van Putten; Sebastian Löbner; Sensory Motor Concepts in Language & Cognition; SFB 991; Sonderforschungsbereich 991; syntactically based relativistic effects; syntax; T. Florian Jaeger; Tagalog; Tundra Yukaghir; verb meaning; volition in Grammar; Whitesands; William A. Foley; yacatec maya; Electronic books; Festschrift; Konferenzschrift -- 2012 -- Düsseldorf